Ways of Buildings Energy Efficiency Increase in EU Countries and Ukraine - Kariuk, Alla; Koshlatyi, Oleg; Lvovska, Ð¢etiana; Pashynskyi, Viktor (International Journal of Engineering and Technology, 2018)
Directions of implementing energy saving and energy efficiency policies in international practice, in particular in European Union countries are considered in the given work. It was defined that in the majority of the countries there occurred a considerable decrease in GDP energy intensity during 1990-2016 due to energy efficient technologies implementing. Investments into energy sphere were considerably increasing under compensation at expense of systemic investment decrease into oil and gas sphere. Investments into energy efficiency according to the world regions are reviewed. It was noted that the highest result in energy efficiency sphere in all the global community are achieved in the European Union (EU). The highest level of import dependence in observed in two strategically important sectors, which are oil and gas. According to the aims and priorities of steady development, energy efficiency is defined as the most effective way of energy security increasing. A review of energy efficiency condition in Ukraine compared to world and European experience was made. Particular attention is paid to the energy efficiency condition in construction.Standards for specific energy consumption as for new buildings are substantially strengthened in EU member states, and calculation procedure for the buildings energy efficiency is obligatory in all countries. It is established that only a complex thermo-modernization of an existing housing stock can significantly affect the reduction of energy consumption.Â Â